The conjunction of non-consciously perceived object identity and spatial position can be retained during a visual short-term memory task - Bergström, Fredrik; Eriksson, Johan (Frontiers in Psychology, 2015)
Although non-consciously perceived information has previously been assumed to be short-lived (< 500 ms), recent findings show that non-consciously perceived information can be maintained for at least 15 s. Such findings can be explained as working memory without a conscious experience of the information to be retained. However, whether or not working memory can operate on non-consciously perceived information remains controversial, and little is known about the nature of such non-conscious visual short-term memory. Here we used continuous flash suppression to render stimuli non-conscious, to investigate the properties of non-consciously perceived representations in delayed match-to-sample (DMS) tasks. In Experiment I we used variable delays (5 or 15 s) and found that performance was significantly better than chance, thereby replicating previous findings. In Experiment II the DMS task required participants to combine information of spatial position and object identity on a trial-by-trial basis to successfully solve the task. We found that the conjunction of spatial position and object identity was retained, thereby verifying that non-conscious, trial-specific information can be maintained for prospective use. We conclude that our results are consistent with a working memory interpretation, but that more research is needed to verify this interpretation.